2019
DOI: 10.1177/1012690219857023
|View full text |Cite
|
Sign up to set email alerts
|

Pleasure and the Sanctuary Paradox: Experiences of girls and women playing soccer

Abstract: Arguably, girls’ and women’s soccer in England is currently experiencing amelioration in terms of participation numbers, media coverage and general public interest. Although, lurking behind these favorable statistics and the pretence of new developmental strategies sits soccer’s cultural millstone, weighing down social progression and limiting the credibility afforded to the game. This paper seeks to unearth how girls and women negotiate their experiences of playing against this backdrop of inferiority by givi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
0
9
0
3
Order By: Relevance
“…The cultural, material, and organizational standing of elite women's football is both similar and different in the United States and England, making for compelling comparison (Dunn, 2016;Markovits, 2019). Gender inequality in football remains a pressing and persistent issue in both countries; women's football lags significantly behind the men's game in mainstream media coverage, contract terms, compensation, and sponsorship (Author; Pielichaty, 2020;Williams, 2007). However, it is undoubtedly also the case that the resources and status accorded to women's elite football in both these countries has grown (Author; Pfister, 2015;Pielichaty, 2020).…”
Section: Background Women's Football In Comparative Perspectivementioning
confidence: 99%
“…The cultural, material, and organizational standing of elite women's football is both similar and different in the United States and England, making for compelling comparison (Dunn, 2016;Markovits, 2019). Gender inequality in football remains a pressing and persistent issue in both countries; women's football lags significantly behind the men's game in mainstream media coverage, contract terms, compensation, and sponsorship (Author; Pielichaty, 2020;Williams, 2007). However, it is undoubtedly also the case that the resources and status accorded to women's elite football in both these countries has grown (Author; Pfister, 2015;Pielichaty, 2020).…”
Section: Background Women's Football In Comparative Perspectivementioning
confidence: 99%
“…Thus, enjoyment is both a positive affective response and a motivating factor in determining and sustaining participation. 22,26 Within educational contexts, enjoyment has also been identified by teachers as an important outcome of planned activities, [27][28][29] with young people consistently citing 'fun' [30][31][32][33] and pleasure [34][35][36] as primary reasons to engage in sports. Furthermore, recent qualitative research has shown that un-creative sport pedagogies can further alienate young people, especially females.…”
Section: Similarly Thomas and Wilsonmentioning
confidence: 99%
“…Fotball føyer seg inn i dette bildet -til tross for endringer i nyere tid: Blant annet økte medieinteressen for kvinnefotball kraftig etter VM i 1999 (Ravel og Gareau 2016). Shugart (2003) som studerte mediedekningen av det amerikanske kvinnelandslaget i forbindelse med mesterskapet, fant imidlertid at seksualisering fortsatt var framtredende, men skjedde på mer subtile måter enn tidligere.…”
Section: Metafortellingen Om Kvinnefotballunclassified
“…Det Amanda reflekterer over er ikke ukjent. Det er en rekke forskningsbidrag som har beskrevet hvordan kvinnefotball dekkes i mindre grad og annerledes enn herrefotball (Shugart 2003;Skogvang 2009; von der Lippe 2010; Ravel og Gureau 2016). Kaelberer (2019) løfter dessuten fram hvordan idrett-media-marked-dynamikken begrenser utviklingen av kvinnefotballen.…”
Section: Kvinnefotball Som Underordnet Herrefotballunclassified
See 1 more Smart Citation